Characterizations Of ZnO Reinforced Poly (3-Hydroxybutyrate) Composites For Electronic Applications - Janakiraman, Vishnu Chandar (2018)
In this work, pure polymer [P(3HB) homopolymer, P(3HB-co-10 mol% 3HHx) copolymer and P(3HB-co-15 mol% 3HHx) copolymer] and its nanocomposite [P(3HB)/ZnO, P(3HB-co-10 mol% 3HHx)/ZnO and P(3HB-co-15 mol% 3HHx)/ZnO] films with seven different concentration of ZnO NPs ranging from 0% to 30% were fabricated using solution casting method. The effect of ZnO NPs on different properties of pure polymer and its nanocomposite films were studied to find its potential applications in electronics field. The XRD analysis clearly confirms the presence of polymer [P(3HB) homopolymer, P(3HB-co-10 mol% 3HHx) copolymer,